A theory of international conflict management and sanctioning - Garoupa, Nuno R. (2022)
In this paper we analyze sanctioning policies in international law. We develop a model of international military conflict where the conflicting countries can be a target of international sanctions. These sanctions constitute an equilibrium outcome of an international political market for sanctions, where different countries trade political influence. We show that the level of sanctions in equilibrium is strictly positive but limited, in the sense that higher sanctions would exacerbate the military conflict, not reduce it. We then propose an alternative interpretation to the perceived lack of effectiveness of international sanctions, by showing that the problem might not be one of undersanctioning but of oversanctioning.